Design of rainwater harvesting district at Kebon Melati Tanah Abang - Rendy; Santoni (ARTEKS : Jurnal Teknik Arsitektur, 2017)
Jakarta’s dense population has caused a disorder in the urban system by negatively impacting its streams. Therefore, this research aims to find out the urban district design criterias with rainwater harvesting system and how to implement them in residential areas of Kebon Melati, Tanah Abang. Data collecting techniques used in this research include literature studies, field observation, and interviews. The proposed solution to Jakarta’s rainwater problems is to design a district which incorporates the four potential urban design theory applications into it. The first theory is about land use related to storage and drainage system. The second theory is about vehicle circulation and pedestrian paths related to roadblock gaps and permeable materials. The third theory is about building mass and shape related to catchment area, conveyance, and green roof. The last theory is about open spaces related to water retention basins. The goal of this urban district design is to develop and decrease the speed of rainwater flow in Kebon Melati.